Al-Madrasat al-Ūlā in the Modern Workplace: Phenomenological Insights into Work–Family Conflict, Islamic Coping, and Role Negotiation among Urban Muslim Mothers - Ratna Wulandari; Elan Sumarna (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: Recent global labour-market shifts have lifted women’s labour-force participation to 54.42 % in Indonesia, compelling Muslim mothers to juggle dual identities as household educators (al-Madrasat al-Ūlā) and paid professionals. This study investigates how urban Javanese Muslim mothers interpret and reconcile these roles, integrating Islamic pedagogy with work–family research. Methods: A phenomenological approach combined 30 semi-structured interviews in three cities with a systematic review of 65 peer-reviewed studies (2010-2024). Inductive thematic coding of transcripts was triangulated with the literature. Main Findings: Role conflict stems mainly from rigid schedules, scarce workplace childcare and entrenched patriarchal norms. Mothers mitigate stress through extended-family help—especially grandmothers—religious coping rituals (dhikr, ṣalāh, majlis ta‘līm) and care-focused micro time-management that privileges “quality spiritual parenting” over duration. The al-Madrasat al-Ūlā ideal persists but is re-imagined as collective moral stewardship shared across family networks. Contribution: The study proposes an “Islamic Coping Matrix” linking context-specific stressors, resources and adaptive behaviours, demonstrating how religious capital compensates for limited institutional support and enriching cross-cultural work–family theory. Conclusion: Harmonising professional and maternal duties is feasible when organisations provide flexible policies and when community institutions—mosques and neighbourhood childcare schemes—augment state provision. Faith-based, culturally attuned interventions can thus sustain Muslim mothers’ dual contributions to household resilience and national productivity.